Anti-psoriatic and Anti-inflammatory Potentials of Phytochemicals from Curcuma longa against Interleukin-17A and Inducible Nitric Oxide Synthase: An In Silico Study - Abdul-Hammed, Misbaudeen; Olajide, Monsurat; Adedotun, Ibrahim Olaide; Afolabi, Tolulope Irapada; Abdul-Razaq, Roqeebah; Ismail, Ubaedah; Abdullateef, Muhminah Folake; Adebayo, Zainab Omowumi (Majalah Obat Tradisional, 2024)
Psoriasis is a chronic autoimmune cell-mediated inflammatory skin disease that affects approximately 125 million people worldwide. Turmeric has been long known for its potent anti-inflammatory activities. In this study, in silico studies were used to evaluate the efficacy of isolated phytochemicals from turmeric in the treatment of psoriasis. One hundred and fifteen phytochemicals from this plant and two standard medications (Flurandrenolide and Triamcinolone), active ingredients used in some topical steroid creams were evaluated for their inhibitory properties against Interleukin-17A (IL-17A) and Inducible NOS (iNOS) receptor using a computer-aided drug design approach. The binding scores and inhibitory efficiencies were obtained via virtual screening. ADMET SAR-2 website was used to conduct the Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) analysis, the Molinspiration and SwissADME tools were used to investigate the drug-likeness characteristics and oral bioavailability of the selected compounds respectively. Other analyses of the selected compounds include bioactivity, activity spectra for substances (PASS) prediction, binding mode, and molecular interaction. The results revealed that Bisabolone (−9.3 kcal/mol), Curcumanolide B (−8.6 kcal/mol), (E)-sesquisabinene hydrate (−8.5 kcal/mol), and procurcumadiol (−8.3 kcal/mol) are potential inhibitors of iNOS receptor, while hop-17(21)-en-3-ol (7.6 kcal/mol) is a potential inhibitor of IL-17A receptor. These compounds have better ADMET properties, binding affinities, drug-likeness, PASS properties, bioactivities, oral bioavailability, good binding mechanism, and interactions with the active site of the target receptor when compared with Flurandrenolide and Triamcinolone. As a result, this preliminary investigation suggests that these phytochemicals should be studied further to design novel psoriasis therapeutics.